@dyputustudio’s Utilization of TikTok as a Self-Photo Studio Promotion to Build Interactions with Consumers - Najwa Dalillah Pratiwi; Metha Madonna (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2024)
In the era of rapid digital transformation, social media platforms have become dominant tools for communication, marketing, and consumer interaction. Among these, TikTok has emerged as one of the most influential spaces for creative digital promotion, particularly for small businesses and creative industries. This study explores @dyputustudio’s utilization of TikTok as a promotional medium for its self-photo studio services, focusing on how the platform is used to build interactions and relationships with consumers. The research employs a qualitative descriptive approach, emphasizing observation, interviews, and documentation analysis to understand Dyputu Studio’s promotional strategies and audience engagement patterns. Findings reveal that TikTok functions not only as a promotional channel but also as a space of social interaction and digital community formation between the studio and its consumers. The platform’s interactivity, algorithmic visibility, and audio- visual creativity enable Dyputu Studio to effectively showcase its self-photo studio services, stimulate audience participation, and cultivate brand loyalty. This study demonstrates that digital communication on TikTok aligns with Pierre Lévy’s New Media Theory, which highlights interactivity, hypertextuality, and networking as key dimensions of modern media engagement. Through consistent content creation, responsive communication, and trend adaptation, Dyputu Studio successfully transforms social media presence into a form of digital relationship marketing. The study contributes to the understanding of how small creative businesses can leverage social media to achieve marketing and communicative goals in the digital era.